2015
DOI: 10.1007/s10450-015-9683-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics of CO2, CO, N2 and CH4 on zeolite LiX pellet and activated carbon granule

Abstract: The adsorption uptake curves of CO 2 , CO, N 2 and CH 4 on zeolite LiX and activated carbon were measured using a volumetric method at 293, 308 and 323 K and pressure up to 100 kPa. The experimental uptake curves were correlated with a non-isothermal kinetic model because the adsorption kinetics was controlled by heat generation and transfer, and an isothermal model showed large deviation from experimental uptake. The adsorption rates of the gases on zeolite LiX and activated carbon were affected by the isoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…In principle, adsorption kinetics can be measured experimentally using a variety of techniques, for example, by monitoring the time-dependence of volumetric or gravimetric sorption capacity [17,18], by the combined pressure-swing and volume-swing frequency response technique [19,20], using a dynamic column breakthrough apparatus [21], and via zero length column (ZLC) experiments [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, adsorption kinetics can be measured experimentally using a variety of techniques, for example, by monitoring the time-dependence of volumetric or gravimetric sorption capacity [17,18], by the combined pressure-swing and volume-swing frequency response technique [19,20], using a dynamic column breakthrough apparatus [21], and via zero length column (ZLC) experiments [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of literature ( Figure 1) revealed that the reported effective sorption rates for N2 and CH4 on commercial adsorbents similar to those measured in this work have large variations, ranging in some cases over two orders of magnitude. Figure 1 Variations in effective sorption rate (D/r 2 ) reported in the literature for N2 and CH4 on activated carbon (AC) [18,21,24,25], zeolite 13X [26][27][28], carbon molecular sieve (CMS) [17,20,29] and zeolite 4A [30][31][32] One possible reason for the large deviations present in the literature data is that kinetic measurements are often analysed under the assumption of a constant temperature throughout the adsorbent, usually on the basis that the sample mass is small ( 1 g). However, the adsorption rate observed in such measurements is generally non-isothermal because heat is evolved during the process and cannot be removed instantaneously due to heat transfer limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption equilibria of N 2 and CO 2 were measured on activated carbon at several temperatures (293–323 K) using a volumetric technique . The adsorption isotherms of N 2 and CO 2 on activated carbon were correlated to the partial pressure of each component at the maximum feed pressure (650 kPa).…”
Section: Resultsmentioning
confidence: 99%
“… Adsorption isotherms of (a) CO 2 and (b) N 2 on activated carbon at (○) 293 K, (△) 308 K, and (□) 323 K …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have attributed increased R soil following precipitation events to physical mechanisms (e.g., displacement of CO 2 stored in dry soil pores (Huxman et al, 2004;Kim et al, 2012;Marañón-Jiménez et al, 2011)) or biological mechanisms (e.g., increased microbial metabolism (Kim et al, 2017)). R soil can also decrease following precipitation events, which has also been attributed to physical (e.g., decreased D gs (Davidson et al, 2000;Kim et al, 2012;Rochette et al, 1991;Šimůnek & Suarez, 1993)) and biological processes (e.g., shift from aerobic to anaerobic decomposition (Ball et al, 1999;Davidson et al, 2000;Kim et al, 2012)).…”
Section: Journal Of Geophysical Research: Biogeosciencesmentioning
confidence: 99%